What are the Sociocultural Factors That Influence the Managerial Performance of Rural Women Entrepreneurs? - Lindokuhle Senamile NTULI (PT Keberlanjutan Strategis Indonesia, 2024)
Women are considered to be an important human resource in South Africa, and every country should try to utilize them as mediators of economic growth and development. Sociocultural factors challenge them to achieve managerial performance. However, the literature focuses on sociocultural research for women in urban provinces of South Africa, neglecting rural women in KZN. On the other hand, sociocultural research usually overlooks the insufficient attention to the needs and challenges faced by women in their enterprises. This study aims to examine the factors influencing rural women's entrepreneurship performance in KwaZulu-Natal (KZN). The study employed a qualitative approach, where open-ended semi-structured interviews were used as instruments for data collection. There were 26 questionnaires distributed to women entrepreneurs operating their businesses in rural KZN, specifically uMhlabuyalingana, eJozini and Big5Hlabisa. Thematic content analysis was the primary method utilized for analyzing the collected data. Findings reveal that these women demonstrate resilience and adaptability in managing business alongside family responsibilities. Strategic planning and conflict management are essential for overcoming challenges, although there is a need for leadership and financial management training. Sociocultural factors, including family responsibilities and varying levels of social support, play a significant role, while gender stereotypes continue to undermine their managerial abilities. Limited access to Technology hinders business growth, stressing the need for digital skills training to enhance efficiency, competitiveness, and market reach. Tailored support programs addressing these sociocultural and technological challenges are essential to enhancing rural women entrepreneurs' success and driving economic development in rural communities.